Предмет: Алгебра,
автор: nberz
распишите прошу это все
Приложения:
Ответы
Автор ответа:
1
(a+b - 2b ) * (a+b) = ((a+b)(a+b) - 2b*a) * (a+b) =
( a a+b) ( a(a+b) )
= (a² +2ab+b²-2ab) * (a+b) = a²+b²
( a(a+b) ) a
( a a+b) ( a(a+b) )
= (a² +2ab+b²-2ab) * (a+b) = a²+b²
( a(a+b) ) a
Похожие вопросы
Предмет: Другие предметы,
автор: евгенидог
Предмет: Українська мова,
автор: GroзnaяУчилка
Предмет: Українська мова,
автор: ivanpetrenko
Предмет: Русский язык,
автор: regermark
Предмет: Биология,
автор: Аноним